2004
DOI: 10.1111/j.1439-0418.2003.00817.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal population interactions between the parasitoids Cotesia flavipes and Tachinidae flies: considerations on the adverse effects of biological control practice

Abstract: Biological control of Diatraea saccharalis is regarded as one of the best examples of successful classical biological control in Brazil. Since the introduction of the exotic parasitoid Cotesia flavipes, the decrease of D. saccharalis infestation in sugarcane fields has been attributed to the effectiveness of this agent. Recently, the native tachinid fly parasitoids (Lydella minense and Paratheresia claripalpis) have also been implicated in the success. Here, we investigated the spatial and temporal population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…At present, D. saccharalis is controlled either by introduction of transgenic cultivars of sugarcane ( Arencibia et al., 1997; Setamou et al., 2002) or by biological control by artificially introduced exotic parasitoid Cotesia flavipes ( Baker et al., 1992). Both methods have undesirable side‐effects on non‐target organisms ( Setamou et al., 2002; Rossi , 2004; Rossi and Fowler , 2004a,b). Implementation of efficient pheromone‐based monitoring system for D. saccharalis might help to minimize the harm.…”
Section: Discussionmentioning
confidence: 99%
“…At present, D. saccharalis is controlled either by introduction of transgenic cultivars of sugarcane ( Arencibia et al., 1997; Setamou et al., 2002) or by biological control by artificially introduced exotic parasitoid Cotesia flavipes ( Baker et al., 1992). Both methods have undesirable side‐effects on non‐target organisms ( Setamou et al., 2002; Rossi , 2004; Rossi and Fowler , 2004a,b). Implementation of efficient pheromone‐based monitoring system for D. saccharalis might help to minimize the harm.…”
Section: Discussionmentioning
confidence: 99%
“…in the study area; however, there is no evidence that releases of C. flavipes triggered a decrease in the activity of these tachinid flies during the study period. Although the work carried out by Weir and Sagarzazu (1998) showed that flies were more effective than wasps in inoculations on D. saccharalis larvae in the laboratory, Rossi and Fowler (2004) observed a marked tendency for populations of the tachinid flies L. minense and B. claripalpis to decrease at sites in Brazil where C. flavipes had been released. However, these studies in the Cauca River Valley are, to the best of our knowledge, the first in Colombia, and additional studies should be conducted on future releases of C. flavipes in relation to population densities of L. minense.…”
Section: Figmentioning
confidence: 95%
“…Despite being less harmful than chemicals, even biological control products should be used with caution. For instance, the massive release of Cotesia flavipes (Cameron, 1891) (Hymenoptera: Braconidae) in sugarcane to control Diatraea saccharalis (Fabricius, 1794) (Lepidoptera: Pyralidae) as part of an ABC program carried out for years in Brazil probably displaced tachinid parasitoid flies from the environment where they used to be commonly found [74]. Such undesirable consequences can also happen in soybeans if a biocontrol agent of stink bug is released or applied abundantly in the fields without adopting a sound ET, especially considering the large area cultivated with this crop (around 45 million hectares in Brazil alone).…”
Section: Recommendations Of Soybean Ipm To Preserve and Increase Biol...mentioning
confidence: 99%